Fracture toughness for longitudinal compression failure of laminated composites at high loading rate. (May 2022) - He, Rui; Gao, Yidi; Cheng, Longfei; Cui, Hao; Li, Yulong
Highlights: The fibre kinking failure of laminate composites was characterized here at loading rate of up to 3.5 m/s. The translation and rotation of the sample were minimized with symmetrical dynamic loading using an electromagnetic Hopkinson bar. Two different tape of damage evolution has been observed in this study depending on the amount of delamination involved. Abstract: Dynamic fracture toughness of laminated composites in fibre kinking mode, and its evolution with crack growth, is characterized in this paper at high loading rate. The compact compression specimen was loaded with electromagnetic Hopkinson bars at a velocity of up to 3.5 m/s. The measured surface displacement/strain fields with digital image correlation were analysed with the J-integral method, and energy dissipation during initiation and propagation of fibre kinking band was obtained at different loading rates. The fracture toughness at the initiation of fibre kinking damage remains constant in all tests, while during kinking band growth stage, it has been found to decrease noticeably at higher loading rate. Two different types of damage evolution have been observed in this study depending on the amount of delamination involved, as delamination can lead to a rapid drop of loading capacity, and results in relatively low fracture toughness after kinking band formation.